INCIDENCE OF ACUTE ISCHEMIC STROKE IN HYPERTENSIVE PATIENTS IN LAHORE, PAKISTAN - Butt, Nauman Ismat; Waris, Barak; Ghoauri, Muhammad Sohail Ajmal; Baber, Asyhveen (Indonesian Journal of Pharmaceutical and Clinical Research, 2025)
This study aimed to determine the incidence of acute ischemic stroke in hypertensive individuals in Lahore, Pakistan, and was conducted at the Department of Medicine, Chaudhary Muhammad Akram Teaching and Research Hospital. Hypertension was defined as blood pressure exceeding 140/90 mmHg on two separate occasions, ambulatory readings above 140/90 mmHg recorded at least 15 days apart, or a known history of antihypertensive medication use. Acute ischemic stroke was defined as sudden loss or weakness in function of one or more limbs on clinical examination, confirmed radiologically by a CT scan of the brain. A total of 200 hypertensive patients aged 18 years and older were included using non-probability consecutive sampling. Participants underwent evaluation for blood pressure control, antihypertensive therapy, comorbidities, and acute ischemic stroke. The results showed that acute ischemic stroke was present in 6.5% of patients. Chi-square analysis revealed that prolonged duration of hypertension, poor hypertension control, current treatment regimen, presence of diabetes mellitus, and ischemic heart disease had statistical associations with stroke. However, in logistic regression analysis, no variable was found to be a significant predictor of stroke. It is concluded that acute ischemic stroke is not an uncommon finding in hypertensive patients, being more prevalent in those with prolonged hypertension duration, poor control, and the presence of comorbidities.